Enhancement of K2P2.1 (TREK1) background currents expressed in Xenopus oocytes by voltage-gated K+ channel β subunits - Kisselbach, Jana; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Life sciences, 2012)
Aims - K2P2.1 (TREK1) two-pore-domain potassium channels control electrical activity in the central nervous system (CNS) and in the heart. Auxiliary β subunits (Kvβ) increase functional K+ channel diversity in the CNS. Based on similar tissue distribution and common functional significance of Kvβ2 protein and K2P2.1 channels in neuronal excitability, we hypothesized that Kvβ2 subunits modulate K2P2.1 currents. - Main methods - Rat K2P2.1 channels and rKvβ subunits were expressed in Xenopus laevis oocytes, and two-electrode voltage clamp electrophysiology was used to assess K2P2.1 function. - Key findings - Kvβ2 subunits increased K2P2.1 currents by 2.9‐fold in concentration-dependent fashion (I0mV,K2P2.1, 0.53±0.07μA; I0mV,K2P2.1+Kvβ2, 1.56±0.13μA; n=15). K2P2.1 channel stimulation resulted in resting membrane potential hyperpolarization by −10.7mV (n=15). Open rectification and current-voltage relationships of K2P2.1 channels were not markedly altered upon co-expression with Kvβ2, and K2P2.1 membrane expression was not affected by Kvβ2 subunits. Related subunits Kvβ1 (1.7-fold; n=16), Kvβ3 (2.2-fold; n=16), and Kvβ4 (2.8-fold; n=16) similarly activated K2P2.1 currents, indicating a broader role for Kvβ proteins in K2P2.1 regulation. - Significance - Kvβ subunits stabilize the resting membrane potential through enhancement of K2P2.1K+ currents. The significance of this previously unappreciated biophysical mechanism in neuronal physiology remains to be investigated.